Binding of the Bi (III) Complex of Naringin with β-Cyclodextrin/Calf Thymus DNA: Absorption and Fluorescence Characteristics. (5th June 2014) - Yousuf, Sameena; Enoch, Israel V. Muthu Vijayan
Abstract : Naringin-Bi (III) complex (Narb) was prepared and analysed by UV-Visible absorption and fluorescence measurements. The inclusion complex of Narb with β -Cyclodextrin ( β -CD) was characterized by the UV-Visible absorption, Infrared, scanning dlectron microscopic, and X-ray diffractometric techniques. The stoichiometry of the inclusion complex of Narb with β -CD was 1 : 1 with a binding constant of 5.18 × 10 2 mol −1 dm 3 . The interaction of Narb with Calf Thymus DNA (ctDNA) was investigated in the presence and the absence of β -CD. The binding constants for the interaction of Narb with ctDNA in the absence and the presence of β -CD were 1.29 × 10 5 mol −1 dm 3 and 6.89 × 10 4 mol −1 dm 3, respectively. The Stern-Volmer constants for the interaction of Narb with ctDNA in the absence and the presence of β -CD were 1.25 × 10 4 mol −1 dm 3 and 5.10 × 10 3 mol −1 dm 3, respectively. The lowering of the binding affinity and the K sv were observed for the interaction of Narb with ctDNA in the presence of β -CD.